External Ear and Submandibular Extracranial Arteriovenous Malformation: A Case Report - Mariapan, Shanthi; Gopal, Sangaran; Negi, Ruchi; Haziqah, Fatin; Tumaisuri, Dinie (New Visions in Medicine and Medical Science Vol. 7, 2024)
Arteriovenous malformation (AVM) are caused by failure of primitive arteriovenous channels to regress during fetal development. Extracranial AVM is a rare entity. The aim of this descriptive study is to show the progressiveness of an extracranial AVM of a patient over the course of 20 years. A 34 years old male, initially presented with a soft compressible at the left ear pinna since age of 15 years old. 6 years later he developed another soft compressible swelling at the left cheek. Further investigations showed arteriovenous malformation from branches of the left external carotid artery with draining veins from left external jugular vein. A suggested treatment of embolization and left pinectomy made the patient worried of disfigurement and he defaulted treatment from Hospital Kuala Lumpur. Last year he had one presentation of blood spurting from his left ear pinna which needed medical attention at Hospital Shah Alam. CT Angiography (CTA) was done and the extent of the disease recorded which involved the terminal branches of external carotid artery for the external ear AVM, which are maxillary artery and superficial temporal artery as well as facial artery for the submandibular AVM, all draining into the external jugular vein. Currently there are more protruding vessels seen at the back of his ear and he was advised to revisit Hospital Kuala Lumpur for treatment option. It is a sign of persistence and progressiveness of his disease. Author was unable to find reported incidence of external ear and submandibular AVM in the same individual, however there was a reported case of infratemporal and parotid AVM. The affected branches were different however it shows there are literature of more than 1 extracranial AVM on the same side but scarce. Follow up of this patient may provide useful in monitoring further vessel dilatation or new AVM cranially or caudally from the branches of the external carotid artery.